Implementasi Market-Day untuk Meningkatkan Pengetahuan Ekonomi Dasar dalam Pembelajaran IPS pada Siswa Kelas VI Sekolah Dasar - Meliana Nesa Aqila; Zahwa Salsabila; Oman Farhurohman (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
This research aims to explore the implementation of Market-Day as a learning medium to improve basic economic understanding for sixth grade elementary school students. Through this activity, students gain practical experience regarding economic concepts such as demand, supply, transactions and financial management. This approach also encourages the development of social skills, creativity and an entrepreneurial spirit, which are relevant to the needs of the era of globalization. Market-Day provides real simulations that integrate economic theory into daily practice, thereby helping students better understand and apply economic values in their lives. This research uses a literature study approach by referring to relevant scientific sources, such as books, journals and research reports. The study results show that Market-Day is not only effective in increasing understanding of economic theory, but also strengthens students' managerial skills and financial awareness. With this experience-based learning, students are taught to be more responsible and innovative, so they are better prepared to face economic challenges in the future. This article concludes that Market-Day is a strategic approach that can be applied in elementary schools to combine economic learning with the development of students' life skills, especially in supporting the Merdeka Curriculum which is oriented towards holistic learning.